A bootstrap-ANFIS framework for oral cancer prognosis based on clinical and genomic markers - Chang, Siow Wee; Sameem, A.K.; Zain, R.B.; Merican, A.F.M.A. (2010)
The incidence of oral cancer is high in Malaysia especially for those of Indian ethnic origin. In this research, an oral cancer prognosis prediction model will be developed by using Bootstrap-ANFIS techniques. The aim of this research is to improve the prediction of oral cancer survival and to identify the key clinical and genomic markers for the survival prediction of oral cancer. The proposed model is designed to handle small medical dataset with limitations in terms of time, cost and tissue samples.